2017
DOI: 10.1186/s13052-017-0401-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances in paediatrics in 2016: current practices and challenges in allergy, autoimmune diseases, cardiology, endocrinology, gastroenterology, infectious diseases, neonatology, nephrology, neurology, nutrition, pulmonology

Abstract: This review reports main progresses in various pediatric issues published in Italian Journal of Pediatrics and in international journals in 2016. New insights in clinical features or complications of several disorders may be useful for our better understanding. They comprise severe asthma, changing features of lupus erythematosus from birth to adolescence, celiac disease, functional gastrointestinal disorders, Moebius syndrome, recurrent pneumonia. Risk factors for congenital heart defects, Kawasaki disease ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 105 publications
(104 reference statements)
1
4
0
2
Order By: Relevance
“…Another study showed that children with acyanotic CHD experienced 4.94 (SD 2.54) episodes of ARI annually, which was significantly higher compared to cyanotic CHD at 2.41 (SD 1.89), (p=0.01). (27) The incidence of ARI episodes in acyanotic left-to-right shunt is significantly higher (5.08 (SD 2.55)) than conotruncal anomaly, which was similar with our findings. Some authors define recurrent ARI as respiratory infections occurring at least six times per year or at least three times per year if it involves the lower respiratory tract.…”
Section: Discussionsupporting
confidence: 92%
“…Another study showed that children with acyanotic CHD experienced 4.94 (SD 2.54) episodes of ARI annually, which was significantly higher compared to cyanotic CHD at 2.41 (SD 1.89), (p=0.01). (27) The incidence of ARI episodes in acyanotic left-to-right shunt is significantly higher (5.08 (SD 2.55)) than conotruncal anomaly, which was similar with our findings. Some authors define recurrent ARI as respiratory infections occurring at least six times per year or at least three times per year if it involves the lower respiratory tract.…”
Section: Discussionsupporting
confidence: 92%
“…Drugs that are not used via a continuous infusion pump and drugs from different classes of cardiovascular system and nervous system, according to the ATC, were excluded. Thirteen drugs used via continuous infusion pump in intensive care units in the treatment of patients using invasive mechanical ventilation, in the treatment of hemodynamic instability and in the maintenance of fluid balance, were selected for the study 11–17 . Such conditions, prevalent in complex patients requiring intensive care 18–20 .…”
Section: Resultsmentioning
confidence: 99%
“…In the first stage of the study, medications widely used by CI in paediatric and neonatal ICU's were selected, which according to level 1 of the Anatomical Therapeutic Chemical Classification (WHO, 2020) were classified as medications for the central nervous system (morphine, ketamine, fentanyl, midazolam and dexmedetomidine), and for the cardiovascular system (epinephrine, norepinephrine, dopamine, dobutamine, milrinone, nitroprusside, nitroglycerin and furosemide) 11–17 …”
Section: Methodsmentioning
confidence: 99%
“…La forme sévère de l'asthme est rare chez l'enfant. Elle représente 5% des enfants asthmatiques [1]. Dans la littérature, selon les données du « Global Initiative for Asthma and the National Asthma Education and Prevention Program Guidelines for the Diagnosis and Management of Asthma » (GINA 2017) [2], l'asthme sévère se définit selon le niveau de traitement nécessaire au contrôle des symptômes et des exacerbations avec souvent nécessité de traitements multiples dont des corticoïdes inhalés à forte dose.…”
Section: Introductionunclassified
“…Dans la littérature, selon les données du « Global Initiative for Asthma and the National Asthma Education and Prevention Program Guidelines for the Diagnosis and Management of Asthma » (GINA 2017) [2], l'asthme sévère se définit selon le niveau de traitement nécessaire au contrôle des symptômes et des exacerbations avec souvent nécessité de traitements multiples dont des corticoïdes inhalés à forte dose. C'est une pathologie hétérogène avec une grande variabilité des manifestations cliniques entre les patients [1,2].…”
Section: Introductionunclassified